Transformasi Perilaku Hidup Bersih dan Sehat Melalui Intervensi Handuk Pribadi di Pondok Pesantren Darul Mukhlisin Kota Malang - Asri, Yuni; Priasmoro, Dian Pitaloka; Handayani, Wiwik (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Personal hygiene is often neglected in Islamic boarding schools due to limited facilities and economic constraints, leading to the sharing of personal items such as towels and increasing the risk of skin infections like scabies and impetigo. Objective: The purpose of this service was to improve clean and healthy living behavior (PHBS) among students at Pondok Pesantren Darul Mukhlisin through education and the distribution of personal clean towels. Method: This public service was conducted using a participatory educational approach. Activities included initial assessments (pre-test), health education sessions, distribution of labeled personal towels, and post-intervention evaluation using questionnaires and observation Result: The number of students who consistently used personal towels increased from 36% to 88%. Knowledge regarding the risks of towel-sharing also improved significantly. Conclusion: This service program effectively transformed student behavior regarding personal hygiene through practical and contextual interventions. The activity is recommended as a replicable model for promoting PHBS in other Islamic boarding schools